2012
DOI: 10.1371/journal.pone.0031658
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Vascular and Hematopoietic Genes Downstream of etsrp by Deep Sequencing in Zebrafish

Abstract: The transcription factor etsrp / Er71 / Etv2 is a master control gene for vasculogenesis in all species studied to date. It is also required for hematopoiesis in zebrafish and mice. Several novel genes expressed in vasculature have been identified through transcriptional profiling of zebrafish embryos overexpressing etsrp by microarrays. Here we re-examined this transcriptional profile by Illumina RNA-sequencing technol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 66 publications
2
23
0
1
Order By: Relevance
“…Whole-mount analyses at 19 and 24 hpf revealed that tmem88a is expressed within the primordial heart field but seems to be more expansively expressed in the emerging vasculature (Fig. 2D,E,I,J), consistent with the findings of Gomez et al (Gomez et al, 2012).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Whole-mount analyses at 19 and 24 hpf revealed that tmem88a is expressed within the primordial heart field but seems to be more expansively expressed in the emerging vasculature (Fig. 2D,E,I,J), consistent with the findings of Gomez et al (Gomez et al, 2012).…”
Section: Resultssupporting
confidence: 89%
“…Interestingly, results from Gomez et al (Gomez et al, 2012) show that Tmem88 is expressed in the posterior mesoderm in the developing vasculature of the zebrafish. In situ hybridization data shown here also indicate that Tmem88 is expressed in the developing vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we noted concomitant reduction in fli1a, fli1b, hey2, lmo2, tal1, kdrl , and flt4 in let-7a duplex-injected embryos (Fig. 5B), consistent with the observation that ectopic Etv2 can induce expression of these endothelial genes in zebrafish embryos (Gomez et al, 2012; Gomez et al, 2009; Wong et al, 2009). Co-injection of etv2 mRNA containing a heterologous 3’UTR along with let-7a duplex rescued the expression of these Etv2-responsive genes, suggesting that they are not directly targeted by let-7a (Fig.…”
Section: Resultssupporting
confidence: 88%
“…The severe early vascular defects and global effects on endothelial gene expression in both mouse and zebrafish embryos suggests that etv2 plays an early role in specifying endothelial cell lineages. Consistent with this possibility, overexpression Etv2 in both zebrafish embryos and mouse embryoid bodies can expand endothelial cell lineages and induce concomitant expression of hundreds of vascular genes (Gomez et al, 2012; Koyano-Nakagawa et al, 2012; Sumanas and Lin, 2006; Wong et al, 2009). Furthermore, recent studies demonstrate that Etv2 is an essential component, along with Fli1 and Erg, during direct endothelial reprogramming of human amniotic cells (Ginsberg et al, 2012).…”
Section: Introductionmentioning
confidence: 72%
“…However, despite the abundance and importance of these regulators in the spatio-temporal control of Rac1 function, little is known about their implication during vascular development24. In particular, CdGAP (Cdc42 GTPase-activating protein)/ARHGAP31, a GAP for Rac1 and Cdc422526, was reported to be highly expressed in human umbilical vein endothelial cells (HUVECs)24, and to be regulated in Zebrafish by the transcription factor Ets, a master regulator of angiogenesis2728. Outside of the vascular system, pro-migratory and pro-invasive functions were ascribed to CdGAP, which was shown to regulate directional membrane protrusions of migrating osteosarcoma cells293031 and TGFβ-dependent cell motility and invasion of breast cancer cells32.…”
mentioning
confidence: 99%